2020
DOI: 10.1039/c9ra08189e
|View full text |Cite
|
Sign up to set email alerts
|

The lamellar structure and biomimetic properties of a fish scale matrix

Abstract: A preparation technology for a fish scale matrix is shown, and its lamellar structure and biomimetic properties are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…22,25 According to our previous research, FS is composed of multilayered collagen bers. 17 The FTIR spectra recorded for FS showed typical bands for type I collagen: amide A, amide B, amide I, amide II, and amide III. We observed that the band amide A has been moved to lower frequencies due to the loss of binding water in collagen and the conformational changes of collagen molecules.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…22,25 According to our previous research, FS is composed of multilayered collagen bers. 17 The FTIR spectra recorded for FS showed typical bands for type I collagen: amide A, amide B, amide I, amide II, and amide III. We observed that the band amide A has been moved to lower frequencies due to the loss of binding water in collagen and the conformational changes of collagen molecules.…”
Section: Discussionmentioning
confidence: 95%
“…The preparation method was based on our previous research. 17 C. idella sh scales about 2.5 cm-diameter and 1000 g weight, were collected (Chengdu, Sichuan Province, China), and then washed at 15 C in turn with distilled water, mixed solvents, and buffers to remove mucopolysaccharides, proteins, and fats. The scales were then immersed in 10% EDTA solution at 4 C for decalcication for about 4 h, then cleaned with water and incubated in acetic acid solution at 4 C for 1 h to obtain the basal plates from the scales.…”
Section: Preparation Of Sh Scales (Fs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In another tissue form a luminous shark, E. spinax, bioluminescence transmittance across the dorsal spine was evaluated to 10 % (5), while in a luminous Gasteropoda, Hinea brasiliana , through a specific shell architecture, the transmittance was measured to 63% (27). Comparatively in a nonluminous freshwater teleost, Ctenopharyngodon idella , a transmittance value of 20–30% was estimated for the dermal scale (28). Our value is in the high range of transmittance suggesting a significant role in light transmission.…”
Section: Discussionmentioning
confidence: 99%
“…These fibers of collagen demonstrate a sliding behavior as the tooth penetrates, which also provides lamellar sliding resulting in tension of the soft fibers and compression of the hard-bony shells (limiting layer), resulting in tooth fracture of hampering (Yang et al, 2014). Similarly, the puncture resistant property in scales of carp and arapaima are found to be advantageous against physical threats, which can resist failure at even strain FIGURE 4 | Orientation of collagen fibers (in red) in eight-layered lamellae of grass carp under SEM (Feng et al, 2020).…”
Section: Effects Of Fish Scale Configuration On Mechanical Propertiesmentioning
confidence: 99%